SUMMARY OF: PORTUGAL ILUSTRADO PELO SEXO FEMININO DE DIOGO MANUEL AIRES DE AZEVEDO (LISBOA, 1734), TRADIÇÃO DO GÉNERO - Avelino, Carla (2019)
The present essay has for it’s main target the presentation of the study and of Diogo Manuel Aires de Azevedo's work, titled Portugal ilustrado pelo sexo feminino, notícia histórica de muitas heroínas portuguesas que floreceram em virtude, letras e armas, published in Lisbon, in 1734. Diogo Azevedo's matter subject - describes the numerous lives of Portuguese Women who distinguish themselves by noble actions - allowing us the insight of the didactic and moral value of their work and by such being part of the long traditional feminine biographies, associated to the hagiographic descriptions.The great diffusion of the theme as began with Boccaccio in De mulieribus claris and proceeded by Juan Perez de Moya, Frei Luís dos Anjos, Damião de Froes Perym and others. We propose to present this study in witch the main objectives is sustained by the desire to bring to the, specific or not , major public's attention a work from the XVIII century, which by it's specifics reveals itself of enormous literature, historic and cultural importance.